Factors that Affect Cesarean Delivers in the General Hospital of Guaranda (Ecuador) - Bayas, Favian (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: Cesarean section is a surgical procedure that involves the removal of the fetus through the abdominal through an incision in the uterus. The most common causes for this practice are maternal, fetal, maternal-fetal, and obstetrics. The recommended percentage of cesarean sections according to the World Health Organization is 10–15%. However, in our country, it exceeds 45%. Considering this, the present work was proposed to study the causes that affect the performance of cesarean sections in the General Hospital of Guaranda. Method: To this end, a retrospective, descriptive, and cross-sectional analysis was performed on a total of 319 patients who underwent cesarean section during the second semester of 2015, an analysis of their respective medical histories was carried out, as well as a direct interview with three gynecologist-obstetrician specialists of the hospital. Results: It was determined that the number of cesarean sections performed was 319 (44%) compared to the number of normal deliveries that were 403 (56%); of the caesarean sections, 63% were emergency due to premature membrane rupture, prolonged labor, fetal distress, and cephalopelvic disproportion, and the remaining 37% was by medical prescription. Conclusion: In conclusion, the physicians consider that the preparatory conditions of the mother significantly influence the practice of a cesarean section.